Two Systems for Targeted Gene Deletion in Coxiella burnetii - Beare, Paul A. (American Society for Microbiology, 2012)
Coxiella burnetii is a ubiquitous zoonotic bacterial pathogen and the cause of human acute Q fever, a disabling influenza-like illness. C. burnetii's former obligate intracellular nature significantly impeded the genetic characterization of putative virulence factors. However, recent host cell-free (axenic) growth of the organism has enabled development of shuttle vector, transposon, and inducible gene expression technologies, with targeted gene inactivation remaining an important challenge. In the present study, we describe two methods for generating targeted gene deletions in C. burnetii that exploit pUC/ColE1 ori-based suicide plasmids encoding sacB for positive selection of mutants. As proof of concept, C. burnetii dotA and dotB, encoding structural components of the type IVB secretion system (T4BSS), were selected for deletion. The first method exploited Cre-lox-mediated recombination. Two suicide plasmids carrying different antibiotic resistance markers and a loxP site were integrated into 5′ and 3′ flanking regions of dotA. Transformation of this strain with a third suicide plasmid encoding Cre recombinase resulted in the deletion of dotA under sucrose counterselection. The second method utilized a loop-in/loop-out strategy to delete dotA and dotB. A single suicide plasmid was first integrated into 5′ or 3′ target gene flanking regions. Resolution of the plasmid cointegrant by a second crossover event under sucrose counterselection resulted in gene deletion that was confirmed by PCR and Southern blot. ΔdotA and ΔdotB mutants failed to secrete T4BSS substrates and to productively infect host cells. The repertoire of C. burnetii genetic tools now allows ready fulfillment of molecular Koch's postulates for suspected virulence genes.